Lipid and lipoprotein concentrations during pregnancy and associations with ethnicity - Christin W. Waage; Ibrahim Mdala; Hein Stigum; Anne Karen Jenum; Kåre I. Birkeland; Nilam Shakeel; Trond M. Michelsen; Kåre R. Richardsen; Line Sletner (BMC, 2022)
Abstract Background To describe ethnic differences in concentrations of lipids and lipoproteins, and their changes, during pregnancy to postpartum. Methods This was a population-based cohort study conducted in primary antenatal care in Norway. The participants (n = 806) were healthy, pregnant women, 59% were ethnic minorities. Outcomes were triglycerides, total cholesterol, HDL- and LDL-cholesterol, analysed from fasting blood samples drawn at gestational age (weeks) 15, 28 and 14 weeks postpartum. We performed linear regression models and linear mixed models to explore the total effect of ethnicity on the outcomes, adjusting for gestational age /week postpartum, maternal age and education. The analyses are corrected for multiple testing using the Bonferroni correction. Results At gestational age 15, triglyceride concentrations were lower in women of African origin (1.03 mmol/mol (95% CI: 0.90, 1.16)) and higher in women of South Asian (primarily Pakistan and Sri Lanka) origin (1.42 mmol/mol (1.35, 1.49)) and East Asian (primarily Vietnam, Philippines and Thailand) origin (1.58 mmol/mol (1.43, 1.73)) compared with Western Europeans (1.26 mmol/mol (1.20, 1.32)). Women of Asian and African origin had a smaller increase in triglycerides, LDL- and total cholesterol from gestational age 15 to 28. At gestational age 28, LDL-cholesterol levels were lowest among East Asians (3.03 mmol/mol (2.72, 3.34)) compared with Western Europeans (3.62 mmol/mol (3.50, 3.74)). Triglycerides and HDL-cholesterol were lower postpartum than at gestational age 15 in all groups, but the concentration of LDL-cholesterol was higher, except in Africans. South and East Asian women had lower HDL-cholesterol and higher triglycerides postpartum, while African women had lower triglycerides than Western Europeans. Conclusion We found significant differences in the concentrations of lipids and lipoproteins and their changes during pregnancy and the early postpartum period related to ethnic origin.